2019
DOI: 10.1002/cncr.32152
|View full text |Cite
|
Sign up to set email alerts
|

Oral testing for high‐risk human papillomavirus DNA and E6/E7 messenger RNA in healthy individuals at risk for oral infection

Abstract: Background Testing for oral high‐risk human papillomavirus (HPV) DNA may be useful for identifying individuals at increased risk for HPV‐driven oropharyngeal cancer (OPC). However, positivity for HPV DNA provides no information on the transforming potential of the infection. In contrast, the detection of high‐risk HPV E6/E7 messenger RNA (mRNA) may help to identify clinically significant infections because of the indispensable role of E6/E7 viral oncoproteins in the carcinogenic process. Methods Oral rinses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…HIV-infected subjects also showed a lower clearance of any HPV compared with the HIV-uninfected MSM, whereas the opposite was observed for high-risk HPVs. Taken together, these data might explain the higher prevalence of any HPV in the HIV-infected subjects of the OHMAR study and the similar prevalence observed for high-risk types in the two study groups 21…”
Section: Discussionsupporting
confidence: 61%
“…HIV-infected subjects also showed a lower clearance of any HPV compared with the HIV-uninfected MSM, whereas the opposite was observed for high-risk HPVs. Taken together, these data might explain the higher prevalence of any HPV in the HIV-infected subjects of the OHMAR study and the similar prevalence observed for high-risk types in the two study groups 21…”
Section: Discussionsupporting
confidence: 61%
“…Of these, 117 were HIV-infected subjects (37.7%), for the most part on cART (110, 94.0%), with a median number of nadir and a current CD4+ T-cell count of 300 (IQR: 202-403) and 636 cells/mm3 (IQR: 473-812), respectively. Sociodemographic and behavioral characteristics of the participants in the OHMAR study were detailed in a previous report [32]. To summarize, HIV-infected subjects were significantly older (median age: 43 vs. 39 years, p = 0.005) and reported a significantly lower number of recent oral sex partners (median of two vs. four, p = 0.003) than the HIV-uninfected counterparts.…”
Section: Study Populationmentioning
confidence: 94%
“…The large majority of these subjects were on combined antiretroviral therapy (cART) (110, 94.0%). With regard to sociodemographic features and lifestyle, the OHMAR study population has been previously described [15]. Briefly, HIV-infected and HIV-uninfected MSM differed significantly with respect to age (median age: 43 vs. 39 years) and number of recent oral sex partners (median of two vs. four).…”
Section: Study Populationmentioning
confidence: 99%
“…Thus, additional studies are needed to thoroughly explore the determinants of infection with the different HPV genera. Compared with the general population, prevalence of oral infection by mucosal HPVs is higher in men who have sex with men (MSM), particularly in those living with HIV-1 infection [8,[11][12][13][14][15]. In a previous study, we showed that beta and gamma HPVs are abundantly present in oral specimens from MSM, and that oral infection by beta HPVs is significantly more common than that caused by alpha types, irrespective of HIV status [6].…”
Section: Introductionmentioning
confidence: 99%